Reviewing the Role Criticality of Culture and Technology in Knowledge Management Practice: From Practitioners' Viewpoint. Issue 1 (June 2019) - Dutt, Himanshu; Kusumawati, Reni Diah
This article is targeting at examining the difference between the impact of culture and technology on the knowledge management (KM) practices. It holds two points: first is why the existing research relies heavily on cultural approach to KM and the second one is why technology view of KM is neglected in the past research. Most scholars have rated organizational culture highly over tech-nology (IT). This premise has been largely made in context of knowledge sharing, with technology enabling this transfer. As KM matured from sharing to creating knowledge, scholarly views, however, have remained unchanged. This stubborn viewpoint—culture precedes technology—weighs behaviours and attitudes, collectively called culture, compared to the technology thus, limiting its scope. This research attempts to find out if KM practitioners agree to this notion. Whose contribution they value more—culture or technology? Our research assessed the role of culture and technology, individually, for their impact/contribution to overall KM practice. We found practitioners testifying against the above hypothesis, giving credit largely to technology for KM success in their organizations, over culture. Our research further outlines the reasons why culture has taken the backseat and what contribution technology has been making to successful KM practice.